Dinamika Śapatha Pada Beberapa Prasasti Era Kerajaan Paṅjalu - Susilo, Juan Steven; Dr. Ni Ketut Puji Astiti Laksmi, SS.,M.Si.; Zuraidah, S.S., M.Si. (Widya Winayata : Jurnal Pendidikan Sejarah, 2024)
Prasasti is a charter given by a figure to an area due to the service of the area to the kingdom, Śapatha is an oath for breaking the King's decrees that have been confirmed in that area. Śapatha itself contains that it will be unlucky for the person to break the decree given by the King in that area. The Śapatha found in the era of the Paṅjalu Kingdom always experienced dynamics. The Śapatha issued by the kings of Paṅjalu paid attention to several aspects, starting from the natural aspect, the cultural aspect, as well as the aspect of proper and heinous punishment for destroyers of sīma status. That the Kingdom of Paṅjalu has dynamics in writing a śapatha Keywords: Dynamics, Śapatha, Raja, Paṅjalu